The effect of network degree on bargaining: Experimental evidence from the field - Ben D'Exelle; Christine Gutekunst; Arno Riedl (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
We conduct an artefactual field experiment in real-existing trade networks to analyze how individual network degree affects bargaining demands and outcomes. We combine data from a bilateral bargaining experiment with data of trade networks in 24 villages in Uganda. To identify the effect of individual degree in the village trade network we experimentally vary the disclosure of participants' identities in a bargaining pair. We state hypotheses on how degree will affect behavior and find partial support for them. Specifically, we observe that individual degree affects bargaining demands in the predicted direction when one of the bargainers is informed about the network positions but not when either no or both sides are informed. Moreover, network degree affects the likelihood of agreements and earnings, irrespective of the knowledge of the network positions of bargaining partners.
Keywords: C78; C90; L14; 330; bargaining; social networks; network degree; experiments